New insights into algae factories of the future. (January 2018) - Raslavičius, Laurencas; Striūgas, Nerijus; Felneris, Mantas
Abstract: The total combined weight of biological material on planet Earth has been estimated in one source at about 75 × 10 9  t. Of this: crops comprise 2 × 10 9  t (2.7%) as well as microbes, fungi, algae and similar types of microorganisms are estimated to comprise over 50% of the total amount. Microalgae is outstanding among all the types of biomass sources in its ability to respond to the challenges of the future in terms of availability, high growth and production rates, yield per unit area, not competing for arable land, being most suitable optimal sources for both liquid and gaseous biofuels and valuable co-products within biorefineries. It is logical that the increased ability to occupy new niches in the energy sector is determined by uptake of the new forms of biomass exploitation coupled with environmental impact reduction. This could explain the worldwide interest in exploiting algal biomass as an ideal attribute for photosynthetic capture of anthropogenic carbon that reached a record high of ~ 10 Pg C yr −1 in 2014. In this review, we outline microalgae's potential to capture carbon in coal-fired power plant, discuss the advantages of photosynthetic organisms as a source for biodiesel and solid biofuel production, discuss the process engineering, different synergies and legislative factors needed to make the process efficient and economically viable. Before commercial-scale installations become feasible, however, numerous points still have to be resolved. In order to identify potentials and obtain recommendations for action, co-authors have studied in detail various options for climate-beneficial recycling and trapping CO2 in the algae factories of the future that potentially could be built in the European humid continental climate countries.